The Effect of Corporate Social Responsibility on Consumer Purchase Decisions with Corporate Image and Brand Image as Intervening - Cici Amalyah Anik Suhartini; Imanda Firmantyas Putri Pertiwi (Profesional Muda Cendekia Publishing, 2021)
This study to measure the influence of social responsibility on consumer purchasing decisions to buy Rabbani products. This research uses quantitative research using multiple linear regression analysis which has 4 studies. The technique of collecting data by distributing questionnaires. Samples were taken as many as 100 respondents who were given to Rabbani customers in the City of Salatiga. The results showed that there was an influence between corporate social responsibility, corporate image and brand image on purchasing decisions. The results of path analysis show that corporate image and brand image mediate corporate social responsibility in purchasing decisions.